Antimicrobial mechanisms of spice essential oils and application in food industry - Li, Yong-xin; Erhunmwunsee, Famous; Liu, Man; Yang, Kunlong; Zheng, Weifa; Tian, Jun (Food chemistry, 2022)
•Introduced the antimicrobial activities of SEOs and their main active components.•SEOs are potential substitute for chemical preservatives.•Summarized the antimicrobial mechanism of SEOs and their main components.•SEOs can be used for active packaging to prevent food spoilage in the food industry. Spice essential oils (SEOs) are commonly used in food flavoring and are considered an effective food preservative. It has a broad range of applications and promising development prospects. As a natural food additive, SEOs’ antimicrobial effects have been widely studied and utilized towards food preservation. Many SEOs have exhibited significant antimicrobial activities against food-borne pathogenic and food spoilage microorganisms. We reviewed the antibacterial and antifungal properties of SEOs, the active components, their corresponding mechanisms of actions, as well as their application in the food industry, providing a theoretical basis for SEOs’ further development and application as natural preservatives.